Influence of traditional earthquake-resistant techniques on the out-of-plane behaviour of stone masonry walls: Experimental and numerical assessment - Murano, Antonio (2019)
The main goal of the work is to assess the efficiency of traditional earthquake resistant solutions to improve the out-of-plane performance of stone masonry walls. Therefore, the present paper presents the results of an experimental campaign and numerical analysis performed on three stone masonry walls with a U-shaped plan configuration. Two of them were built with traditional earthquake-resistant techniques usually found in European Mediterranean area, namely steel ties and timber-laced reinforcements embedded at the corners of the walls. These techniques are specifically intended to enhance wall-to-wall connections and, thus, improve the out-of-plane behaviour of the walls. The experimental campaign included qualitative assessment procedures, non-destructive tests for the material characterization and a quasi-static test for the characterization of the out-of-plane response. Additionally, a finite element numerical model was built, calibrated with the experimental results, allowing to perform a parametric study to evaluate the influence of the number of reinforcements and geometrical configuration on the out-of-plane behaviour of stone masonry walls.